Bacterial Contamination of Street Vended Food Pani Puri Available in Janakpurdham, Dhanusha - Yadav, Nagendra Prasad; Yadav, Rakesh Kumar; Prakash, Satyam (Tribhuvan University Journal of Microbiology, 2019)
Objectives: To determine the level of bacterial contamination in food (Panipuri) available in market of Janakpur, Dhanusha, Nepal. Methods: Total 120 samples of Panipuri (60 solid matters and 60 masalaa Pani) collected aseptically from the market were transported to the microbiology laboratory and processed for microbial count by serial dilution technique. Microbial load and presence of pathogen were detected in each sample. Results: Analysis of the food samples revealed that 70% of Panipuri samples had high loads of bacterial pathogens such as Escherichia coli, Staphylococcus aureus, Klebsiella spp, Pseudomonas spp, Bacillus spp. Conclusion: This study depicted that the street vended food Panipuri of Janakpur are highly contaminated with pathogenic bacteria which can cause health risk to consumers. Thus, it is suggested that regular monitoring of the quality of street foods must be practiced to avoid any food bone illness in future.